(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Sugar cane or tebu (Saccharum officinarum L.) is useful in Hinduism ceremonies in Bali, so that the people plant it in the home yard. Its population is not big but it spreads all over Bali. The farmers use it to be the merchandise at the markets, especially for the ritual ceremonies uses. The use of sugar cane in ritual ceremonies is very popular as symbolize of wedding ceremony. The sugar cane is put in front part of the cars when they go to the bride’s house for the permission. The sugar cane stem cut into two parts used as the parts of the offering, as the tegen-tegenan as the offering as the earth product, raka-raka fruit for canang/offering, pedangal for tooth ceremony etc. The research was conducted in Tabanan Bali to know the varieties of sugar cane and the function in ritual ceremony in Bali. The result showed that people used 8 kinds of sugar cane for the ceremonies such as: tebu ratu/raja, tebu tiying, tebu kuning, tebu selem/cemeng/hitam/ireng, tebu malem, tebu tawar, tebu salah, and tebu suwat. They had function as identities, offering, worship, protection, and food of white cows. This showed that Balinese people had a little knowledge of sugar cane as the offering and the plantation is not maximal. The belief of the sugar cane function in ritual ceremony in Bali supports its reservation. For that it needs to build reservation and introduce new varieties, the clearness of the sugar cane meaning as the facilities of the ceremony and the availability of young sugar cane. Keywords: sugar cane, Balinese, ritual ceremony.